2016
DOI: 10.1016/j.fuel.2016.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical prediction the removal of mercury from flue gas by MOFs

Abstract: Removal of mercury from flue gas has been considered as one of the hot topics in both the scientific and industrial world. Adsorption of elemental mercury (Hg 0) and oxidized mercury species (HgCl2, HgO, and HgS) on a novel metal organic framework (MOF) material, named Mg/DOBDC, with unsaturated metal centers was investigated using density functional theory (DFT) calculations. The results show that Hg 0 stably physi-sorbed on the unsaturated metal center (magnesium ion) of Mg/DOBDC with a binding energy (BE) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 64 publications
(74 reference statements)
0
8
0
3
Order By: Relevance
“…[9] So far, only a handful of computational calculations have focused on the application of MOF for mercury sensing and adsorption. [53,74] Similar computational support should be provided in designing new MOF-based materials with specific targets, incorporation of more adsorption sites on the framework for example, of mercury sensing and adsorption. Additionally, many reports ascribed the quenching or enhancing effect for mercury sensing to the ligand-metal and/or metal-ligand electron transfer.…”
Section: Discussionmentioning
confidence: 99%
“…[9] So far, only a handful of computational calculations have focused on the application of MOF for mercury sensing and adsorption. [53,74] Similar computational support should be provided in designing new MOF-based materials with specific targets, incorporation of more adsorption sites on the framework for example, of mercury sensing and adsorption. Additionally, many reports ascribed the quenching or enhancing effect for mercury sensing to the ligand-metal and/or metal-ligand electron transfer.…”
Section: Discussionmentioning
confidence: 99%
“…Siendo importante contemplar grupos como los tioéteres para futuros estudios de adsorción de mercurio y al grupo fosfina como un posible retenedor de plomo. Sin embargo, para los demás análisis de este estudio, nos centramos en el ligando modificado con el grupo tiol, ya que se ha reportado su uso en especies orgánicas con la finalidad de detectar y/o retener mercurio inorgánico y/u orgánico (Hadi et al, 2015;Huang et al, 2018;Liu et al, 2016;Yee et al, 2013). Además, considerando que el tamaño del poro puede ser determinante para que ciertas redes organometálicas puedan adsorber de manera preferencial especies de mercurio (Jia et al, 2013), es posible que el grupo tioeter debido a una mayor voluminosidad en comparación del grupo tiol, en una posible ROM, en lugar de favorecer la adsorción de Hg 2+ sea un impedimento al disminuir el tamaño de poro.…”
Section: Pardo-rodriguezunclassified
“…Many studies have indicated that a new material, metal organic framework material (MOF), has a good prospect of mercury removal due to its high porosity, large specific surface area and diverse structural morphology [6,7]. HKUST-1 is a copper-based MOF material with each Cu 2+ binds to a water molecule.…”
Section: Introductionmentioning
confidence: 99%